Gaya Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru - Neni Siti Mariam; Kun Nurachadijat (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Every leader has a leadership style that is different from one another. Viewpoints on certain issues become individual leadership capacities. It is undeniable that being a leader must be responsible and have a heavy and influential role. However, everything can be overcome if he uses tactics and strategies according to the situation. The principal is a person who plays an important role in the education process, because the progress of a school depends on the existence of the principal who acts as a leader. The relationship between the principal and the teacher is very important to run an Educational Institution properly. Good cooperation between school principals and teachers can have a positive impact on student academic achievement because it creates a conducive learning atmosphere. Through the right leadership style, the principal must always provide work motivation to teachers so they can maximize teacher performance in learning.